Taking God to court: Job’s deconstruction and resistance of dominant ideology - Swart, Ilse; Saleem, Yasir (2023)
Using poststructural criticism, we explore how the book of Job deconstructs the deed/consequence nexus that stands at the core of the Hebrew Bible’s theological framework – i.e. the doctrine of reward and punishment. Building on both Derridean deconstruction and Foucauldian resistance, we show that the book of Job refuses to comply with the opposite binary of reward and punishment. First, we demonstrate how the friends in their speeches enforce the binary and, thereby, exercise power over Job. Secondly, we consider Job’s resistance and deconstruction of this binary through both his lived experience and desire to argue with God. Finally, we argue how Job’s desire to argue with God challenges God to defend themself in court. In God’s answer, however, one is introduced to a different God than as portrayed by Job’s friends. Moreover, God’s boastful reply, which lacks any justification for Job’s suffering, makes God appear fragile and weak. As such, this article argues that the book of Job may not merely deconstruct dominant ideology, but also God itself.
Keywords: deed/consequence nexus; Retributive Justice; Resistance; Deconstruction; poststructural criticism; Book of Job